The 12-Item Pruritus Severity Scale – Determining the Severity Bands - Stępień, Katarzyna; Reich, Adam (Frontiers in Medicine, 2020)
Introduction: Assessment of pruritus still remains a challenge due to its subjective character. Various itch questionnaires are widely used to evaluate the severity of pruritus. The aim of the current study was to define the cut off values for the 12-Item Pruritus Severity Scale (12-PSS). Methods: A total of 240 patients (86 males and 154 females) in the age between 19 and 87 years (mean 52.9±20.7 years) suffering from pruritic dermatological conditions were asked to assess their maximal pruritus with the 12-PSS, the Verbal Rating Scale (VRS) and the Numerical Rating Scale (NRS). All subjects also completed the Dermatology Life Quality Index (DLQI). VRS, NRS and DLQI scorings were used as anchor measures to define cut-offs of 12-PSS. Results: According to VRS, 43 (17.9%) patients suffered from mild, 96 (40%) from moderate, 65 (27.1%) from severe and 36 (15%) from very severe pruritus. Mean 12-PSS scoring for each VRS category was 7.6±3.9, 10.4±3.9, 13.0±3.8 and 13.9±3.8 points, respectively (p<0.001). Each VRS category significantly differed from the others regarding the mean 12-PSS scoring, except the mean scoring of severe and very severe pruritus (p=0.72). Thus, three pruritus severity categories of 12-PSS were defined with following score ranges: mild pruritus – 3-6 points of 12-PSS, moderate pruritus – 7-11 points of 12-PSS and severe pruritus – 12-22 points of 12-PSS based on calculation of weighted κ coefficient against VRS, NRS and DLQI as anchor measures. Conclusions: The 12-PSS is able to differentiate between patients suffering from mild, moderate and severe pruritus.